Organizational support enhances nurses’ work-family enrichment: a person–context interactionist perspective - Xu, Hao; Zhao, Xiufang (Frontiers in Psychiatry, 2024)
Attaining a favorable work-life balance is a complex and ongoing challenge in the nursing profession. According to a person-context interactionist perspective and the two-factor theory, this study investigated the underlying mechanism by which organizational support impacts work-family enrichment via protective factors (i.e., decent work) and depleting factors (i.e., burnout) among Chinese nurses. A descriptive cross-sectional research design was utilized in this study, employing an online questionnaire as the primary method for data collection. The study included 355 nurses who completed a self-reported questionnaire designed to measure variables such as organizational support, decent work, burnout, work-family enrichment, and demographic information. The collected data were analyzed using a chain mediation model in PROCESS macro (Model 6). The findings of the analysis revealed that nurses reporting higher levels of organizational support also exhibited a greater sense of work-family enrichment. Moreover, the study identified indirect effects of organizational support on work-family enrichment, mediated by decent work and burnout. These findings suggest that targeted interventions aimed at promoting organizational support can contribute to the overall well-being and work-life balance of nurses.